Asbestiform amphiboles in a marble quarry: A case study from the province of Córdoba (Argentina) - Locati, Francisco (2014)
Fil: Locati, Francisco. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.